Isolation and identification of Aphanomyces species from natural water bodies and fish farms in Selangor, Malaysia - Afzali, S.F.; Hassan, M.D.; Abdul-Rahim, A.M.; Sharifpour, I.; Sabri, J. (Penerbit Universiti Kebangsaan Malaysia, 2013)
This study was conducted to isolate and identify fresh water fungi species from the Malaysian natural water bodies and fish farms and to examine the pathogenicity of the isolates as a confirmative identification tool for epizootic ulcerative syndrome (EUS) outbreak in Selangor state, Malaysia. For this aim, 165 water samples and 62 infected fish collected from 12 stations were tested in which 35 and 24 samples were found to be positive for fungi contamination and/or infection, respectively. The isolates were morphologically characterized; from 59 isolates, 32 were identified as Saprolegina, 21 as Achlya and 6 as Aphanomyces species. Experimental infection was carried out by intramuscularly injection of the Aphanomyces spp. isolates to the Malaysian moonlight gourami (Trichogaster Microlepis), where no mortality and no signs of EUS were observed in the fish groups. Histopathology test also revealed no signs of damage in the skin, muscles and other tissues following infection with the isolates indicating that all the Aphanomyces isolates were non-pathogenic.